Analyse Et Illustration De La Valeur Indicatrice Des Espèces Macrobenthiques Du Delta De l’Ouémé Au Bénin - Zinsou, Léonce Herman; Agadjihouedé, Hippolyte; Gnohossou, Pierre; Lalèyè, Philippe (European Scientific Journal, ESJ, 2017)
In this work, it was matter of determining the species characteristics of the delta of the Oueme through the illustration of their indicative value. Sampling was carried out in eight heterogeneous stations covering the periods of flood and low water. The various indices including that of biserial correlation IndVal (Indicator Value Index) and the cover sites of groups were used as the basis of analysis. The results showed that the selected significant indicative species are highly correlated and have a preference for stations full of organic and mineralized matter. Also, taxa have a marked preference for the flood season (21 taxa) than low water (5 taxa). Most characteristic taxa highlighted by this procedure should be useful to assess changes in quality of the plants studied. Most taxa characteristics highlighted by this procedure should be useful to assess changes in quality of the plants studied.